Advances in Developments and Trends of UAV Technology in the Context of Precision Agriculture - Mingxia Li; Jiyu Li (Agriculture)
Agriculture, as a core pathway for advancing modern agricultural development, emphasizes data-driven perception and intelligent decision-making. Unmanned aerial vehicles (UAVs), with advantages such as high-resolution imaging, flexible deployment, and adaptability to diverse terrains, have become an essential tool in this domain. This Editorial synthesizes the key findings from nine representative studies featured in this Special Issue, focusing on recent advancements in UAV-based remote sensing, flight control, and precision spraying. The results indicate that the integration of multispectral imagery with deep learning models significantly enhances crop identification and parameter inversion accuracy. Flight control performance has been greatly improved through innovations such as free-tail configuration optimization and fuzzy sliding mode composite control, ensuring stable operations in complex environments. In the realm of precision spraying, progress in wind vortex regulation and airflow modeling has led to improved droplet deposition consistency and target accuracy. Overall, UAV technologies demonstrate strong potential for cross-disciplinary integration and scalable application, offering robust support for the intelligent transformation of agricultural production.